Comparison of language learning strategies of Iranian college level students in EFL and ESL settings / Jalal Kamalizad - Jalal, Kamalizad (2015)

(untitled)
The main purpose of this study was to investigate and compare language learning strategy (LLS) use pattern of Iranian college level English learners in EFL (English as a foreign language) and ESL (English as a second language) environments and through different groups of proficiency. Exploring the participants’ views on some language learning related issues such as language use and language learning obstacles within both EFL and ESL environments was another purpose of this study. A total of 157 Iranian students participated in the survey. Twelve Iranian students, six from each setting group, participated in the semi-structured interviews. The data were collected and analyzed in separate parts: (1) quantitative analysis, which discussed the data gathered by the Strategy Inventory for Language Learning (Oxford, 1990) survey (SILL), (2) qualitative analysis, which contained the results of semi-structured interviews concerning ESL/EFL Iranian language learners’ views on some critical language learning related issues in EFL/ESL settings. The results of statistical analyses, namely, one-way and two-way ANOVA, MANOVA, and t-test revealed that Iranian ESL learners significantly performed better than Iranian EFL learners on the overall SILL, on the six strategy categories of the SILL, and on individual strategies listed in the SILL. The results also showed that while language proficiency group factor significantly affected the ESL learners in using both the overall SILL and its six categories, it did not significantly differentiate between low, intermediate and advanced EFL learners with respect to overall use of SILL and its six strategy categories. The results of the interview analysis indicated that EFL and ESL groups considerably differed from each other with regard to using language outside the class, and the obstacles placed in their iii path to learning and using the target language in and outside the classroom in their related settings. The main theoretical implication of the study is that learners’ use of LLSs is influenced by their cognitive stance as well as social settings in which strategies are applied.